COMBINATION OF ULTRAVIOLET RADIATION OF AUTOLOGOUS BLOOD, NEGATIVE PRESSURE WOUND THERAPY, AND ENDOLYMPHATIC ANTIBACTERIAL THERAPY IN THE TREATMENT OF POST-TRAUMATIC WOUND INFECTIONS - Zubakha, A.B.; Lihonenko, O.V.; Chorna, I.O.; Shumeiko, I.A.; Storozhenko, O.V.; Skotarenko, T.A.; Yaroshenko, R.A. (World of Medicine and Biology, 2021)
The doctrine of the wound process is one of the current problems of surgery. It reflects the level of theoretical and practical medicine development. The purpose of this work was to study the improvement of treatment outcomes in patients with post-traumatic wound infections. A set of tools was used to treat patients: endolymphatic antibacterial therapy, ultraviolet irradiation of autologous blood and topical application of vacuum therapy. At the present stage, the best topical treatment method in bulky infected and purulent wounds is vacuum therapy using special technical equipment. The proposed complex of treatment reduces the severity of the disease and accelerates the debridement and regeneration of wounds. As a result, it allowed reducing the course of antibiotic administration by 1.8 times and the duration of inpatient treatment by 3.5 days compared to the traditional treatment methods.